Frequency of breast cancer in palpable breast lump - Afshan Nafees, M. Ghayasuddin, Saima Shabbier, Kinza Fatima, Wahbnoorzia, Umm E Farwa, S. Alisha Ali Zaidi, Muhammad Hasan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast cancer is one of the most common types of cancer in women. In the past few decades, its prevalence has increased exponentially. Aim: To evaluate the frequency of breast cancer in our setup. Method: A descriptive cross-sectional study was conducted at K.V.S.S. SITE Hospital, Karachi for the period of 6 months from January 2022 to June 2022. The sample size for this study was 95 patients.The tru-cut biopsy was performed, using a tru-cut gun on patients with BI-RADS 3 clinically suspicious and family history positive.The data obtained was analyzed on the latest version of the SPSS Statistics version 26 (IBM Corp., Armonk, NY, USA). The frequency and percentages of the categorical variables were calculated. Result: A total of 95 female patients presented with palpable breast lumps. The age group presented most commonly with the lump was 32-42 years (40%).The variables like smoking, drinking, raised BMI, history of any cancer, family history of breast or any other cancer, and oral contraceptive use were found to be statistically significantly associated with the malignancy related to the breast (p <0.001). Practical implicaion: This study provides the incidence of the breast cancer which will help the doctors assess every women presenting with the breast lump and provide the required treatment early so that worst outcomes can be avoided. Conclusion: The palpable breast lump should be assessed on an immediate basis and further workup should be conducted in such patients for early diagnosis and improved treatment of the breast cancer. Keywords: Breast lump, Breast cancer, Breast biospy, frequency of breast lump, young women, family history